Disease activity decrease is associated with improvement in work productivity over 1 year in early axial spondyloarthritis (SPondyloArthritis Caught Early cohort). (7th October 2017) - van Lunteren, Miranda; Ez-Zaitouni, Zineb; Fongen, Camilla; Landewé, Robert; Ramonda, Roberta; van der Heijde, Désirée; van Gaalen, Floris A.
Abstract: Objectives: To assess if a change in disease activity is associated with a change in work productivity loss (WPL) over 1 year in early axial SpA (axSpA) patients. Methods: Baseline and 1 year data of axSpA patients in the SPondyloArthritis Caught Early cohort were analysed. Linear regression models were built explaining the change in the Ankylosing Spondylitis Disease Activity Score (ASDAS) over time by the change in absenteeism, presenteeism, WPL and activity impairment over time. Effect modification and confounding were tested for age, gender, arm of Assessment of SpondyloArthritis international Society classification criteria, HLA-B27, duration of chronic back pain, profession and medication. Results: At baseline, in 105 axSpA patients (48% female, mean age 30.8 years, mean symptom duration 13.6 months, 92% HLA-B27 positive, 24% radiographic sacroiliitis), the mean ASDAS was 2.4 (s .d . 1.0), absenteeism 9% (s .d . 23), presenteeism 33% (s .d . 28), WPL 36% (s .d . 30) and activity impairment 37% (s .d . 25). After 1 year, the mean ASDAS decreased to 2.0 (s .d . 0.8) and absenteeism, presenteeism, WPL and activity impairment improved to 6% (s .d . 22), 26% (s .d . 26), 27% (s .d . 29) and 27% (s .d . 26), respectively. Models showed that if ASDAS decreased 1 unit, absenteeism, presenteeism, WPL and activity impairment improved by 5, 17, 16 and 18%, respectively. The impact of disease activity on work productivity was higher in patients with shorter symptom duration and the impact on absenteeism was higher in patients starting pharmacological treatment. Conclusions: In early axSpA patients, work productivity and daily activities are seriously impacted at baseline and 1 year. However, decreasing disease activity is associated with marked improvements in work productivity and daily activities.